Evaluation of CO2 Adsorption Parameters in Fluidised Zeolite 13X Beds Using Non-Linear Multivariate Optimisation - Alessio Caravella; Giuseppe Prenesti; Salvatore De Luca; Maria Turano; Flaviano Testa; Rossella Girimonte (Separations, 2023)
This work is part of a research project aimed at studying potential sorbents for CO2 capture. The main parameters characterising the adsorption process of zeolite 13X were derived with the aim of overcoming the limits of experimental analysis and thus predicting the performances of the materials of interest. In particular, the main parameters that control the adsorption process of CO2 in zeolite 13X were evaluated through parametric optimisation. This systematic procedure allows for the prediction of the performances of the materials at different operating conditions, identifying the most suitable ones for the case under consideration. Another important application lies in the possibility of a preliminary study of a potential process scale-up for future industrial use. The captured carbon dioxide can be stored or used as a reagent in the production of products with higher economic values, such as methanol, DME and others.